Elasticity of Demand for Canadian Exports - Malach, Vernon W. (The Review of Economics and Statistics, 1957)
THIS paper reports the results of a statistical study of the elasticity of foreign demand for Canadian exports. It sprang from the desire to obtain some criterion of the effect on export receipts of altering the exchange value of the Canadian dollar. Attention was centered on merchandise exports since, aside from Chang's attempts to measure the elasticity of the world demand for Canada's exports,' very little work seems to have been done on the export side. The Department of Trade and Commerce has made estimates of the Canadian import elasticities but it regularly treats exports as an exogenous factor in its models of the Canadian economy. This study was conducted intermittently during the last six years. During this time many different approaches to the subject were made.2 The results of what seem to be the most fruitful approach attempted so far are presented here, with only occasional references to previous attempts. This last approach is based primarily upon the statistical work of Schultz, Stone, and Horner, and the contributions to the pure theory of demand of Knight and Friedman. An attempt has been made to fashion the statistical approach so that the concepts we attempt to measure coincide as closely as practicable to the theoretically ideal ones. The first section of the paper deals with some fundamental general considerations which influenced the decision as to what statistical techniques to adopt. Sections II and III summarize the statistical findings and the last takes up some qualifications.